Highly fluorescent few atoms silver nanoclusters with strong photocatalytic activity synthesized by ultrashort light pulses - Santillán, Jesica María José (2020)
While there are conventional chemical synthesis methods to generate metal nanoclusters (NCs), many of them are adversely affected by the unavoidable contamination of the nanoproduct solution, resulting in aggregation, background noise in analytical chemistry, toxicity, and deactivation of the catalyst. In this work, physical method of ultrafast laser ablation as a “green” synthesis approach together with mechanical centrifugation to obtain silver NCs, simplifying widely the chemical synthesis requirements, is proposed. Remarkably, compared with conventional methods for synthesizing Ag NCs, this new approach starts with a colloid that contains nanosized particles as well as smaller species, managing to obtain colloids with few atoms NCs by centrifugation. Those colloids were analyzed by fluorescence spectroscopy observing UV bands corresponding with HOMO-LUMO cluster transitions. Besides, independent HRTEM measurements were made confirming the presence of few atoms Ag NCs, as well as small NPs in different formation stages. Equally important, photocatalytic efficiency of the obtained NCs was studied through degradation of Methylene Blue (MB) when it was mixed with as-prepared or highly centrifuged colloid, showing an enhanced photocatalytic efficiency of 79% as compared to 57% for pure MB after 180 min of illumination. Consequently, this work contributes to establishing a simple approach to synthesize highly fluorescent and photocatalytic NCs.